Associação dos paramêtros crononutricionais com a ingestão total de energia e de macronutrientes ao longo da gestação: estudo de coorte prospectivo - Carrijo, Laura Reis (2022)
Introduction: Recent studies in the field of chrononutrition that link the circadian clock to metabolic physiology and nutrition have shown that eating at times that go against the body's natural circadian rhythms, such as the inactive/sleep phase, leads to a negative impact on metabolism. night with worse glycemic, insulinemic and lipemic response. However, there are still few studies that have studied whether the temporal aspects of diet are associated with the amount of calories and macronutrients ingested by pregnant women. Objective: Analyze the association between chrononutritional parameters and total daily intake of energy and macronutrients from the beginning to the end of pregnancy. Material and Methods: A prospective cohort study was carried out with 100 pregnant women in which data were collected once in each gestational trimester. Food consumption data were obtained in each quarter through three 24-hour food recalls. The chrononutritional variables evaluated were meal and snack times, feeding duration, overnight fasting, number of eating episodes, caloric midpoint, interval between the end of sleep and the first meal, and the last meal and the beginning of sleep. Linear regression analyzes adjusted for confounding factors were performed to associate each of the chrononutritional variables – independent variable – with the total daily intake of energy and macronutrients – dependent variable – in each gestational trimester. Results: In the first and third trimesters, a positive association was found with total caloric intake, protein, fat and carbohydrates at dinnertime, except for the intake of calories from protein in the third trimester. In all gestational trimesters, a positive association was found with calorie intake from fat and dinner time. There was also a positive association between total caloric, fat and carbohydrate intake with the duration of eating and the number of eating episodes. The other chrononutritional variables were associated, but not in all gestational trimesters, except for nighttime snacks, which were not associated. Conclusion: Chrononutritional parameters related to late feeding were associated with higher total caloric intake during pregnancy. The later time of dinner, longer duration of feeding and greater number of eating episodes demonstrated an impact on the higher total daily intake of energy and macronutrients from the beginning to the end of pregnancy.